Facilitating the Adoption and Evolution of Digital Technologies Through Re-conceptualization - Tekkis, Nicholas Pari; Richmond-Smith, Rebecca; Pellino, Gianluca; Kontovounisios, Christos (Frontiers in Surgery, 2022)
Background: The NHS has been making steps towards greater efficiency and cutting costs to maintain quality of care despite constraints, but without innovation the NHS will not be able to meet its increasing financial demands. The purpose of this article is to analyse a single potentially transformative technology’s path of adoption in the NHS (3D printing). Method: Analysis of 3D printing (3DP) and its current value propositions. Re-conceptualization of the technology to gain insights into these value propositions and identify the capabilities it may provide. Analysis of previous business models to identify where this value is not fully captured and development of a new business model, followed by exploration of benefits and potential limitations of this new model. Results: 3DP applications can be broadly categorised into anatomical modelling, implants and tools. Conceptualizing 3D imaging using the layered architecture model suggests the potential of 3DP to evolve the current imaging and modelling infrastructure of the NHS, and as such should be adopted to facilitate this potential. Conclusion: 3DP is an innovation with large potential for generativity, and it is important that it is integrated at a level that could both stimulate and communicate its benefits. Re-conceptualisation identified a backbone within the NHS that could facilitate it as a point of entry, and the most successful installations have been through this channel. However, progress on the frontier is currently limited by both physical and organisational boundaries, the resolution of which is paramount for the current and future success of this technology.